Impact of 5G in Agricultural Networks: A Review of Improvement Strategies and Publication Trends - Alfred Kgopa (AI Society & STMIK Indonesia, 2026)
This study presents a systematic literature review of the impact of fifth-generation (5G) wireless networks on agriculture, focusing on publication trends, challenges, and opportunities from Scopus papers published between 2015 and 2025. The findings reveal a rapid annual growth rate of 34.93% in research outputs, with 274 documents published across 96 sources, indicating rising global interest in 5G-enabled smart farming technologies. However, persistent challenges include infrastructural limitations in rural farm areas, high costs of implementation, and digital literacy gaps among smallholder farmers. The bibliometric analysis highlights strong international collaboration (28.47%) and dominant contributions from India, China, and the USA. Emerging research trends focus on artificial intelligence (AI), edge computing, and hybrid connectivity models, signaling future directions for 5G-based agricultural innovations. Beyond mapping publication trends, this study synthesizes technical integration pathways and policy-relevant strategies for deploying resilient 5G-enabled agricultural networks in underdeveloped regions.